Case Report: ASXL1, RUNX1, and IDH1 mutation in tyrosine kinase-independent resistant chronic myeloid leukemia progressing to chronic myelomonocytic leukemia-like accelerated phase - Oyogoa, Emmanuella; Streich, Lukas; Raess, Philipp W.; Braun, Theodore (Frontiers in Oncology, 2023)
Although the majority of patients with chronic myeloid leukemia (CML) enjoy an excellent prognosis tyrosine kinase inhibitor (TKI) therapy, resistance remains a significant clinical problem. Resistance can arise from mutations in the kinase domain of ABL preventing drug binding, or due to ill-defined kinaseindependent mechanisms. In this case report, we describe the case of a 27-year-old woman with a longstanding history of chronic phase (CP) CML who developed kinase-independent resistance with mutations in ASXL1 and RUNX1. As a consequence of uncontrolled disease, she progressed to a chronic myelomonocytic leukemia-like (CMML) accelerated phase (AP) disease with the acquisition of a mutation in IDH1. This disease progression was associated with the development of an inflammatory serositis, a phenomenon which has been described in CMML but not in AP-CML. This case presents key features of kinase-independent resistance with insight into potential mechanisms, highlights management challenges and describes a novel systemic inflammatory response which occurred in this patient upon disease progression.